The vanishing half [compact disc, unabridged] - Bennett, Brit (Penguin Audio, 2020)
Separated by their embrace of different racial identities, two mixed-race identical twins reevaluate their choices as one raises a black daughter in their southern hometown while the other passes for white with a husband who is unaware of her heritage.